Penguatan Kapasitas Tenaga Kesehatan Gigi Melalui Edukasi Growth Mindset Untuk Meningkatkan Adaptabilitas Dan Resiliensi - Atikah; Tiara; Surya Perdana; Sri Hartini (CV. Multi Kreasi Media, 2026)
Growth mindset refers to the belief that the abilities, intelligence, and skills of healthcare professionals can be developed through effort, dedication, and continuous learning. In the context of a dynamic and high-risk healthcare environment, this mindset plays a crucial role in fostering resilience and adaptability toward changes in procedures, technological advancements, and clinical challenges. This community service activity aimed to enhance the understanding and skills of dental healthcare personnel in developing an adaptive and resilient growth mindset. The program was conducted offline on December 16, 2025, at the Dental Health Academy of Ditkesad, employing lecture, discussion, training, and simulation methods. The materials covered included the concept of growth mindset, adaptive and resilient behaviors, and motivation in carrying out professional responsibilities as healthcare workers. The results showed an improvement in participants’ understanding of growth mindset and its relationship with adaptive and resilient attitudes in facing workplace challenges. Furthermore, participants demonstrated initial abilities to apply the growth mindset through case simulations and interactive discussions. By strengthening a growth mindset and engaging in continuous self-development, participants are expected to be better prepared to face professional challenges, improve their competencies, and achieve their career goals with greater confidence and focus.